The Effect of Mechanical Ventilation on TASK-1 Expression in the Brain in a Rat Model - Na, Buqi; Zhang, Hong; Wang, Guangfa; Dai, Li; Xia, Guoguang (Canadian Respiratory Journal, 2017)
Background and Objective. TWIK-related acid-sensitive potassium channel 1 (TASK-1) is closely related to respiratory central control and neuronal injury. We investigated the effect of MV on TASK-1’s functions and explored the mechanism using a rat model. Methods. Male Sprague-Dawley rats were randomized to three groups: (1) high tidal volume (HVt): MV for four hours with Vt at 10 mL/kg; (2) low Vt (LVt): MV for four hours with Vt at 5 mL/kg; (3) basal (BAS): anesthetized and unventilated animals. We measured lung histology and plasma and brain levels of proteins (IL-6, TNF-α, and S-100B) and determined TASK-1 levels in rat brainstems as a marker of respiratory centre activity. Results. The LISs (lung injury scores) were significantly higher in the HVt group. Brain inflammatory cytokines levels were different to those in serum. TASK-1 levels were significantly lower in the MV groups (P=0.002) and the HVt group tended to have a lower level of TASK-1 than the LVt group. Conclusion. MV causes not only lung injury, but also brain injury. MV affects the regulation of the respiratory centre, perhaps causing damage to it. Inflammation is probably not the main mechanism of ventilator-related brain injury.